Tilt sensitivity for a scalable one-hectare photovoltaic power plant composed of parallel racks in Muscat. Issue 1 (31st December 2022) - Marzouk, Osama A.
Abstract: Using the desktop tool (Energy3D) for modelling sustainable buildings and solar power generation, this work predicts the performance of a scalable photovoltaic (PV) power plant composed of south-facing parallel racks in Muscat (the capital of the Sultanate of Oman, latitude 23.6 degrees North). The pilot PV power plant has 3, 535 PV panels of peak capacity 300 Wp, leading to a total theoretical peak capacity of 1, 060.5 kWp. It covers a land area of 10, 000 square meters (1 hectare). The work focuses on the sensitivity of the output electricity to the tilt of the PV panels. The analysis shows that a fixed year-round optimum tilt angle offers 6.6% less annual yield than the single-axis-horizontal tracking system (continuously varying tilt). Adopting a dual-tilt system (tilt of 8.6 degrees during April–September and 38.6 degrees during October–March) reduces this gap to 2.5%. The PV power plant can provide an annual yield of 1.794 GWh under a dual-tilt setting, and 1.92 GWh with single-axis-horizontal solar tracking. Some results are provided on a per-square-meter basis, for easy estimation of land needs. The accuracy of estimating electric annual yield was tested by benchmarking with the Global Solar Atlas (GSA) online tool by the World Bank, for the case of fixed optimum tilt.